2010
DOI: 10.18785/gcr.2201.03
|View full text |Cite
|
Sign up to set email alerts
|

Do Small, Patchy, Constructed Intertidal Oyster Reefs Reduce Salt Marsh Erosion As Well As Natural Reefs?

Abstract: AbstrAct:One ecological service that oyster reefs provide is stabilization of shorelines through reduced wave energy and erosion from boat traffic, storms, and predominant wind direction. Additionally, increasing sedimentation can enhance the growth of emergent marsh vegetation which further stabilizes unconsolidated sediments. A 21 mo study of constructed (with only 30-35% coverage) and natural oyster reefs in 3 bayous in the Grand Bay National Estuarine Research Reserve (NERR) suggested constructed reefs ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For example, a marsh fronted by an oyster reef sill or breakwater may show greater accretion or decreased erosion (Gittman et al 2016;Smith et al 2018;Chowdhury et al 2019). Restored or constructed oyster reefs have been shown to reduce erosion of salt marsh edges as well or better than natural oyster reefs, showing that they contribute to shoreline stabilization (Stricklin et al 2010;Ridge et al 2017) while others have shown that they may only be effective under certain conditions (La Peyre et al 2017;de Paiva et al 2018). Nonetheless, if restored or constructed oyster beds can protect salt marsh sediments, they will protect the carbon stored within that ecosystem as well, improving the carbon sequestration of the entire coastline (Ridge et al 2017).…”
Section: Carbon Accumulation Ratementioning
confidence: 99%
“…For example, a marsh fronted by an oyster reef sill or breakwater may show greater accretion or decreased erosion (Gittman et al 2016;Smith et al 2018;Chowdhury et al 2019). Restored or constructed oyster reefs have been shown to reduce erosion of salt marsh edges as well or better than natural oyster reefs, showing that they contribute to shoreline stabilization (Stricklin et al 2010;Ridge et al 2017) while others have shown that they may only be effective under certain conditions (La Peyre et al 2017;de Paiva et al 2018). Nonetheless, if restored or constructed oyster beds can protect salt marsh sediments, they will protect the carbon stored within that ecosystem as well, improving the carbon sequestration of the entire coastline (Ridge et al 2017).…”
Section: Carbon Accumulation Ratementioning
confidence: 99%
“…Hundreds of miles of shorelines are protected throughout the United States in efforts to stabilize and prevent the loss of coastal lands, including marshes ( Restore America’s Estuaries, 2015 ). While there are a multitude of approaches used for shoreline protection, recent focus on the use of natural and self-sustaining systems has promoted the development of fringing oyster reefs within estuarine systems ( La Peyre et al, 2014 ; Scyphers et al, 2011 ; Stricklin et al, 2009 ). Oyster reefs are promoted as they may combat marsh erosion by altering water flow patterns and attenuating waves ( Borsje et al, 2011 ), and trapping and stabilizing sediment ( Walles et al, 2015a ; Walles et al, 2015b ; Van Leeuwen et al, 2010 ; Meyer, Townsend & Thayer, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fringing oyster reefs, a recommended Living Shorelines structure, are becoming a more common erosion mitigation method. Studies conducted in Alabama, Louisiana, Mississippi, and North Carolina have shown that these reefs help reduce the impact of waves on the shoreline, increase sediment size, and enhance the growth of seagrass (Stricklin et al 2009;Piazza et al 2005;Meyer et al 1997, Scyphers et al 2011, all of which are major variables in stabilizing marsh shorelines. The majority of these studies suggested that oyster reefs are most effective in low energy environments, such as lagoons and shallow bays, and have little to no effect in higher energy areas.…”
Section: Coastal Erosionmentioning
confidence: 99%
“…Four previous studies, summarized below, have investigated the efficacy of oyster reefs as a form of erosion control. These studies concluded that reefs are successful in this capacity though only in low energy environments (Piazza et al 2005, Stricklin et al 2009. Each study approached oyster reef erosion control with different objectives in various locations ( Figure 2).…”
Section: Oyster Reefs As Erosion Controlmentioning
confidence: 99%